Efficiency and safety of vitrification of surplus oocytes following superovulation: a comparison of different clinical indications of oocyte cryopreservation in IVF/ICSI cycles - Fu, Xiao; Zhang, Yiting; Gao, Shuli; Gao, Shuzhe; Zhang, Meng; Gao, Shanshan; Ma, Jinlong; Chen, Zi-Jiang (Frontiers in Endocrinology, 2023)
Objective: To evaluate the effectiveness and safety of utilizing the small number of remaining vitrified oocytes after the failure of adequate fresh sibling oocytes. The outcome of present study would provide more comprehensive information about possible benefits or disadvantage to cryopreserve supernumerary oocytes for patients who have plenty oocytes retrieved. Methods: This retrospective cohort study included 791 IVF/ICSI cycles using 6344 oocytes that had been vitrified in the Reproductive Hospital affiliated to Shandong University between January 2013 and December 2019.They were divided into three groups: SOC group (supernumerary oocytes cryopreservation), relative-MOC group (relative male factor-oocyte cryopreservation), and absolute-MOC group (absolute male factor-oocyte cryopreservation). Laboratory and clinical outcomes were analysed, and multivariate regression analysis was used to study the effect of different indications of vitrification on CLBR. Results: The CLBR was highest in absolute-MOC, and lowest in SOC (39.0% vs 28.9%, P=0.006)；however，after adjusting for confounding factors，the difference was not statistically significant. Multivariable regression analysis showed no impact of indications of vitrified oocytes on CLBR according to controlled age, BMI, preservation duration, use of donor sperm or not, use of PESA/TESA or not, number of oocytes retrieved, number of oocytes thawed, and oocyte survival rate. The preliminary data of safety showed no significant differences in the perinatal and neonatal outcoms after ET and FET between the SOC and MOC groups. Conclusion: Different indications of vitrification did not affect CLBR. The CLBR of vitrified oocytes for different indications was correlated with age and number of warmed oocytes. For women who have plenty oocytes retrieved，the strategy of cryopreserving a small number of oocytes is a valuable option and might benefit them in the future. Additional data from autologous oocyte vitrification research employing a large-scale and variable-controlled methodology with extending follow-up will complement and clarify the current results.